Selection diversity measurements in a multi-beamformer testbed for wireless networks - Co, Paul Jason R. (2005)
This research deals with the development of a multi-beamformer testbed for diversity measurements. The testbed is composed of an antenna array, a beam forming network, data acquisition block, and computer interface. The testbed is able to measure and acquire the carrier envelope of 2 to 4 simultaneous channels. Measured data is then transferred to a computer where the data is processed. Experiments were conducted in an indoor environment. Induced mobility was introduced to produce a repeatable dynamic channel. Measurements were also made for Line of Sight (LOS) and Non-Line of Sight situations between the transmitter and the receiver. A butler matrix was designed and fabricated to serve as a beamforming network to produce 4 independent simultaneous directive beams, which corresponds to 4 independent channels. Measurements using this beamforming network were made and compared with measurements using omni-directional antennas. Experimental results have shown that the use of 4 simultaneous directional beams produce a gain of 2dB over a system using 2 omnidirectional antennas.